Imagining native America in music - Pisani, Michael V. (Yale University Press, 2005)
This book offers a comprehensive look at musical representations of native America from the pre-colonial past through the American West and up to the present. The discussion covers a wide range of topics from the ballets of Lully in the court of Louis XIV to popular ballads of the 19th century; from 18th-century British-American theatre to the musical theatre of Irving Berlin; from chamber music by Dvorak to film music for Apaches in Hollywood Westerns. Michael Pisani demonstrates how European colonists and their descendents were fascinated by the idea of race and ethnicity in music, and he examines how music contributed to the complex process of cultural mediation. Pisani reveals how certain themes and metaphors changed over the centuries and shows how much of this 'Indian music', which was and continues to be largely imagined, alternately idealised and vilified the peoples of native America.